The Role of Personal Branding and Customer Experience at Warung Kopi Asiang Pontianak - Michael Swintio Halim; Daniel Hermawan (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The purpose of this research is to analyze the role of personal branding and customer experience at Warung Kopi Asiang Pontianak. Design/methodology/approach: The method used is a quantitative method using questionnaire to 100 respondents with convenience sampling technique. Findings: The results showed that customer experience have a contribution in purchase decision at Warung Kopi Asiang Pontianak. However, personal branding that build based on Asiang as owner no give significant contribution in purchase decision. Research limitations/implications: This research is limited to Warung Kopi Asiang in Pontianak. Practical implications: This research can give a comprehensive perspective about personal branding and customer experience in heritage coffee shop. Originality/value: This paper is original. Paper type: Research paper.